W. W. Bryden and the Reformed Protestant Tradition in Canada - Vissers, John A. (Toronto journal of theology, 1990)
In his anniversary retrospect of the Canadian Theological Society, W.O. Fennell reminds us that there were theological forerunners to the present society of Canadian theological scholars. Among them was Walter Williamson Bryden and the Trinitarian Society which met at Knox College during the 1930S and 1940s[…] The 'Barthian scholar' taught church history and theology at Knox College in Toronto from 1925 until his death in 1952, serving as principal of the college from 1945 until 1952. By reflecting the changes occurring in contemporary theology and by introducing the implications of those themes into the Canadian context, Bryden's work as a teacher and theologian is to be noted in the history of Canadian theology as one who sought to maintain a voice for the Reformed Protestant tradition.